Monolayer Two‐dimensional Molecular Crystals for an Ultrasensitive OFET‐based Chemical Sensor. (29th January 2020) - Li, Haiyang; Shi, Yanjun; Han, Guangchao; Liu, Jie; Zhang, Jing; Li, Chunlei; Liu, Jie; Yi, Yuanping; Li, Tao; Gao, Xike; Di, Chongan; Huang, Jia; et al.
Abstract: The sensitivity of conventional thin‐film OFET‐based sensors is limited by the diffusion of analytes through bulk films and remains the central challenge in sensing technology. Now, for the first time, an ultrasensitive (sub‐ppb level) sensor is reported that exploits n‐type monolayer molecular crystals (MMCs) with porous two‐dimensional structures. Thanks to monolayer crystal structure of NDI3HU‐DTYM2 (NDI) and controlled formation of porous structure, a world‐record detection limit of NH3 (0.1 ppb) was achieved. Moreover, the MMC‐OFETs also enabled direct detection of solid analytes of biological amine derivatives, such as dopamine at an extremely low concentration of 500 ppb. The remarkably improved sensing performances of MMC‐OFETs opens up the possibility of engineering OFETs for ultrasensitive (bio)chemical sensing. Abstract : Kleines Sensibelchen : Poröse und nichtporöse Monolagen‐Molekülkristalle (MMCs) von NDI3HU‐DTYM2 wurden durch Drop‐Casting auf verschiedene Substrate hergestellt. Auf beiden MMC‐Sensoren basierende organische FETs sprechen empfindlich auf NH3 ‐Dampf an. Das poröse MMC zeigt eine relative Sensitivität von 72 % bei 0.1 ppb NH3, während sich die Fluoreszenzintensität bei 10 ppb NH3 um 40.9 % verringert.